A Validated Rp-Hplc Method For The Determination Of Linezolid In Pharmaceutical Dosage Forms - K.JAYA PRASANTI; B. SYAMA SUNDAR (International Journal of Pharma and Bio Sciences, 2012)
A simple, precise, rapid and accurate Reverse phase HPLC method was developed for the estimation of Linezolid in tablet dosage form. A Thermohypersil C-18 column (250x4.6 mm, 5 μ) particle size with mobile phase consisting of mixture of Acetonitrile and water in the ratio of 60:40 ( v/v) at pH 6.0 adjusted with ortho-phosphoric acid. The flow rate was 1.0 mL/min and the effluents were monitored at 254 nm. The retention time was 3.27 min. The detector response was linear in the concentration of 20-60 mcg/mL. The respective linear regression equation being y=98.543x+180.061.The limit of detection and limit of quantification was 0.5mcg/mL and 0.17mcg/mL respectively. The percentage assay of Linezolid was 99.94%. This method has been validated and shown to be specific, sensitive, precise, linear, accurate, rugged, robust and fast. Hence this method can be useful for the routine determination of Linezolid in bulk drug and in its pharmaceutical dosage form.